Eyes and Ears: Cross-Modal Interference of Tinnitus on Visual Processing - Li, Zhicheng; Gu, Ruolei; Zeng, Xiangli; Qi, Min; Cen, Jintian; Zhang, Shuqi; Gu, Jing; Chen, Qi (Frontiers in Psychology, 2018)
The visual processing capacity of tinnitus patients is worse than normal controls, indicating cross-modal interference. However, the mechanism underlying the tinnitus-modulated visual processing is largely unclear. In order to explore the influence of tinnitus on visual processing, this study used a signal recognition paradigm to observe whether the tinnitus group would display a significantly longer reaction time in processing the letter symbols (Experiment 1) and emotional faces (Experiment 2) than the control group. Signal detection and signal recognition, which reflect the perceptual and conceptual aspects of visual processing respectively, were manipulated individually in different conditions to identify the pattern of the cross-modal interference of tinnitus. The results showed that the tinnitus group required a significantly prolonged reaction time in detecting and recognizing the letter symbols and emotional faces than the control group; meanwhile, no between-group difference was detected in signal encoding. In addition, any gender- and distress-modulated effects of processing were not found, suggesting the universality of the present findings. Finally, follow-up studies would be needed to explore the neural mechanism behind the decline in speed of visual processing. The positive emotional bias in tinnitus patients also needs to be further verified and discussed.